Effect of Pre-Marital Care Educational Program on Knowledge and Attitude of Female University Students - Hala A. Ali; Amany M. Ahmed; Heba K. Ghazy (Evidence-Based Nursing Research)
Context: Health and well-being before marriage help to maintain the health of future children. Therefore, healthcare should begin before marriage through premarital care as it can recognize and modify health risk factors well-known to have adverse effects on pregnancy outcomes.